Urgensi Pemenuhan Hak Biologis Narapidana Ditinjau Dari Undang-Undang Nomor 22 Tahun 2022 Tentang Pemasyarakatan dan Hak Asasi Manusia - Bramandita, Riki (Fakultas Syariah INSURI Ponorogo, 2023)
This study aims to examine the urgency of fulfilling the right to search biology in the context of Law Number 22 of 2022 concerning Corrections and Human Rights. The research method used is a normative juridical research method, by conducting a literature study and analysis of related documents. Based on the research results, the fulfillment of the right to fulfill biological needs is a very important need and must be a priority in the correctional system in Indonesia. Protection of debilitating biological rights not only impacts health and daily life, but also impacts the health and safety of society as a whole. Law Number 22 of 2022 concerning Corrections and Human Rights has regulated the protection of rehabilitation rights, including biological rights. However, the implementation of the law still needs more attention and improvement. Concrete actions are needed from those responsible for ensuring that biological rights are fulfilled, such as increasing access to health services, improving environmental conditions in prisons, improving the quality of food provided, ensuring protection against acts of violence, and providing sufficient attention to mental health assistance. . In addition, there is also a need for cooperation between various related parties to increase the fulfillment of the biological rights of the request.